Bleeding management after implementation of the Hemorrhage Code (Code H) at the Hospital Israelita Albert Einstein, São Paulo, Brazil - Jaures,Michele (2020)
ABSTRACT Objective To describe the implementation of a care protocol based on rapid response teams, for management and resolution of bleeding. Methods A hospital protocol called Hemorrhage Code (Code H) was devised and developed. In a flow line, a multidisciplinary team provides comprehensive, fast and effective care to the patient with a severe hemorrhagic condition. In another flow line, professionals based at the hospital pharmacy focus on identifying patients at risk of bleeding, to avoid this event. Several hospital professionals and sectors were trained, each with specific roles, ensuring full support to the medical and nursing staffs. Results After implementing this protocol, we were able to significantly reduce the number of catastrophic events related to failure in bleeding management. Conclusion Code H is an example of a value-based medicine and precision medicine project by delivering comprehensive and multidisciplinary care, in addition to point-of-care testing introduced in clinical practice, optimizing patient safety and care practices at the hospital. Furthermore, it will be possible to minimize the risk of lawsuits for the hospital and physicians, as well as rationalizing resources with benefits for administrators and payers.